Do agricultural productive services alleviate farmland abandonment? Evidence from China rural household panel survey data - Tian, Yuan; Gao, Yanlei; Pu, Chenxi (Frontiers in Environmental Science, 2023)
As an important means to solve “who will farm” and “how to farm” in the future, agricultural productive services can change the allocation structure of agricultural factors and play an important role in alleviating farmland abandonment. This study uses the 2017 China Rural Household Panel Survey data and adopts the logistic model, IV Tobit model, and the mediating effect model to investigate the quantitative impact and mechanism analysis of agricultural productive services on farmland abandonment. The results show: (1) Agricultural productive services significantly reduces farmland abandonment by 1.51% on average. (2) Mechanism analysis implies that agricultural labor substitution, land transfer effect, and technological adoption effect play important intermediary roles in alleviating farmland abandonment. (3) Moreover, compared with the eastern region, central region, and non-karst region, agricultural productive services failed to reduce the farmland abandonment in western region and karst region with poor terrain conditions. Agricultural productive services could alleviate the farmland abandonment of small farmers and elderly farmers. Therefore, agricultural productive services contribute to the reuse of small-scale plots.